Root plasticity and xylem modifications drive drought resilience in okra [Abelmoschus esculentus (L.) Moench] at the seedling stage - Kaur, Sukhjiwan Jeet; Talekar, Nilesh; Upadhyay, Priyanka; Singh, Shailesh Kumar; Kumari, Monika; Saini, Dinesh Kumar; Krishna, Bal; Lalotra, Shivani; Ayoubi, Habiburahman (Frontiers in Plant Science, 2025)
Okra [Abelmoschus esculentus (L.) Moench] plays a vital role in ensuring food and nutritional security in arid and semi-arid regions; however, its growth is severely limited by drought stress. While root plasticity and physio-biochemical responses are known to contribute to drought resilience, their specific roles in okra remain underexplored. This study assessed drought tolerance in 55 okra genotypes subjected to three levels of PEG 6000-induced osmotic stress (0%, 10%, and 20%) under polyhouse conditions. Drought stress delayed germination and significantly reduced key growth parameters, including leaf number, shoot length, fresh and dry biomass, and survival rate. Root traits such as secondary root number, root length, and fresh root weight also declined, although the root-to-shoot ratio increased under severe stress, indicating an adaptive shift in biomass allocation. Biochemical analyses revealed elevated levels of chlorophyll, carotenoids, and proline in response to drought, reflecting enhanced stress tolerance mechanisms. Based on overall performance, genotypes G51 (Sonam), G6 (HAU-480), G10 (Bhindi Champion), and G45 (Pooja-01) emerged as the most drought-tolerant, exhibiting superior root development and biomass accumulation. Oxidative stress markers, MDA and H2O2, also increased significantly under severe drought, further validating physiological damage and supporting the classification of tolerant and susceptible genotypes. Principal component analysis identified the mean productivity index and tolerance index as key contributors to genotypic variation under stress. Additionally, Field Emission Scanning Electron Microscopy (FESEM) revealed genotype-specific xylem adaptations, with reduced vessel size in drought-tolerant genotypes likely mitigating the risk of embolism. These findings highlight the importance of root plasticity, xylem architecture, and biochemical adjustments in conferring drought tolerance in okra. Prioritizing traits such as secondary root formation and reduced xylem vessel size offers promising avenues for breeding resilient okra cultivars suited to water-limited environments.